(untitled) (Advancements in Homeopathic Research, 2022)
INTRODUCTION Pain is a sensory, psychological, subjective feeling with or without tissue damage. BACKGROUND Homoeopathy aims ‘cure’ means disappearance of pain with treatment of underlined cause by considering ‘person as a whole’ because just providing relief by any means of suppression is not ‘cure’ . Homoeopathic medication for pain is based on : 1) Proper observation. 2) Totality of symptoms. 3) Pharmacological reasearches. 4) Reports got in drug proving and clinical experiences. 5) Individualisation. 6) Miasmatic background. 7) Materia medica 8) Repertory In homeopathy the symptoms of mind are very important, if the prescription based on that i.e. on mentals and when the remedy would be an anti-psoric then that may cure the case completely. Mentals can be judged through observations and not that what patients would tell. Homeopathy can handle trauma and injury more effectively if we know how to tackle the situations in acute and sub-acute conditions which people refer them as emergency. Such as mental condition of a heart attack patient or his physical distress will guide you to a remedy like Aconite for his fear of death, anxiety and anxiousness. The homeopathic remedies are faster to act than of allopathy in acute conditions also. We can select the perfect remedy from Repertory and Materia medica because they contain already proved and variefied drugs.